Food Consumption Management in Urban Households in Indonesia - Jangkung Handoyo Mulyo; Sugiyarto Sugiyarto; Hani Perwitasari; Arif Wahyu Widada; Fatkhiyah Rohmah; M. Khalifatul Ardhi (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
The most significant contributor to the increase in food waste in Indonesia is household sectors, mainly urban areas. One approach to reducing food waste is Food Consumption Management (FCM). However, the application of FCM at the household level is strongly influenced by various aspects. This study aims to determine the relationship between socio-economic aspects and food consumption management at the urban household level conducted in four major cities in Indonesia during the Covid-19 pandemic. Primary data was collected using a digital questionnaire distributed to households in Medan, Yogyakarta, Surabaya, and Denpasar. A total of 149 household respondents were obtained and analyzed descriptively. Meanwhile, the relationship between socio-economic aspects and the management of food consumption was analyzed using the Pearson correlation method. The results of this study reveal that household income and the number of family members are significant factors closely related to household food consumption management (FCM), especially in terms of providing, storing, and disposing of food waste.